2004
DOI: 10.2746/0425164044868620
|View full text |Cite
|
Sign up to set email alerts
|

The β‐agonist clenbuterol in mane and tail hair of horses

Abstract: Summary Reasons for performing study: The β2‐agonist clenbuterol is commonly administered for therapeutic purposes in the horse, but its use an an anabolic agent is illegal. Clenbuterol can be detected in blood and urine for a relatively short period after administration and detection in hair could enhance the analytical range and be used to determine the history of clenbuterol application. Hypothesis: That detection in mane or tail hair is possible over an extended period. Methods: Four horses received 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 10 publications
4
39
0
1
Order By: Relevance
“…Clenbuterol is a basic lipophilic compound which binds on the hair pigment melanin. Therefore, a strong and permanent incorporation into hair was reported . In spite of its low therapeutic dosages, single or occasional therapeutic administration permits the detection of clenbuterol in pigmented hair as shown in a previous application study with four horses .…”
Section: Introductionmentioning
confidence: 88%
“…Clenbuterol is a basic lipophilic compound which binds on the hair pigment melanin. Therefore, a strong and permanent incorporation into hair was reported . In spite of its low therapeutic dosages, single or occasional therapeutic administration permits the detection of clenbuterol in pigmented hair as shown in a previous application study with four horses .…”
Section: Introductionmentioning
confidence: 88%
“…If the physical location of a steroid residue in a hair strand can be accurately determined, it should be theoretically possible using the presumed growth rate of the hair to calculate an approximate time of administration. In thoroughbreds, mane hair appears best suited for this purpose, with a steady growth rate of around 2.4 cm/month [50,51]. Less suitable are tail hair, which grows more sporadically, and coat hair, which grows comparatively slowly and with considerable seasonal variation.…”
Section: Hairmentioning
confidence: 99%
“…Research on agonists found in cattle and human hair has shown that hair can be considered a good matrix to determine the presence of ␤-agonist in living animals [10][11][12][13][14][15]. However, previous studies have focused mainly on clenbuterol, and data regarding the depletion of RAC residues in sheep hair remain inadequate.…”
Section: Ractopamine (Rac) 4-[3-[[2-hydroxy-2-(4-hydroxyphenyl) Ethymentioning
confidence: 99%